The Shifting Concept of American National Security across History : An Analytic Study - Moussaoui, Islam; Souici, Abdelhadi (University of Eloued جامعة الوادي, 2024)
This research aims to explore how the concept of US national security has evolved, especially with regard to the foundations, structures and perceptions of security in the United States of America from several points of view, the study also explores the applications of national security policy inside and outside the United States of America in its dual uses and multiple methodology. The work also deals with the historical structure and evolutionary processes of the US National Security Council, in particular the tasks of the council and the crucial decisions made. This paper discusses the key periods of nationalism and security in the United States in chronological order, covering key areas such as the early republic, the manifest destiny of the United States, and American participation in world events. It also examines how major events such as the new world order envisioned by George H. W. Bush, the September 11 attacks, and George W. Bush's policy of preemption affect U.S. national security strategies. The evidence presented in the work reveals that the dangers and conditions in the international system are constantly changing, which affects the idea of American national security. This work plays an important role in the development of security studies based on its rich details on the complexities and processes of national security. يهدف هذا البحث إلى استكشاف كيفية تطور مفهوم الأمن القومي الأمريكي، خاصة فيما يتعلق بأسس الأمن وهياكله وتصوراته في الولايات المتحدة الامريكية من عدة وجهات نظر، تستكشف الدراسة أيضا تطبيقات سياسة الأمن القومي داخل وخارج الولايات المتحدة الامريكية في استخداماتها المزدوجة ومنهجيتها المتعددة. يتناول العمل أيضا الهيكل التاريخي والعمليات التطورية لمجلس الأمن القومي الأمريكي، لا سيما مهام المجلس والقرارات الحاسمة التي تم اتخاذها. يناقش هذا البحث الفترات الرئيسية للقومية والأمن في الولايات المتحدة بترتيب زمني، مع تغطية مجالات رئيسة مثل الجمهورية المبكرة، ومصير الولايات المتحدة الواضح، والمشاركة الأمريكية في الاحداث العالمية. كما يفحص كيف تؤثر الأحداث الكبرى مثل النظام العالمي الجديد الذي تصوره جورج بوش الأب، وهجمات 11 سبتمبر، وسياسة الاستباق لجورج بوش الابن على استراتيجيات الأمن القومي الامريكي. تكشف الأدلة الواردة في العمل أن الأخطار والظروف في النظام الدولي متغيرة باستمرار، مما يؤثر على فكرة الأمن القومي الأمريكي. يساهم هذا العمل بدور هام في تطوير دراسات الأمن بناء على تفاصيله الغنية حول تعقيدات وعمليات الأمن القومي.
Literature and Civilization
Keywords: US National Security Council; Cold War; historical analysis; interventionism; isolation.; مجلس الأمن القومي الأمريكي، الحرب الباردة، التحليل التاريخي، التدخلية، العزلة.